Some disease management practices for bacterial wilt of potato (The Journal of Plant Protection Sciences, 2020)
Bacterial wilt [c.o. - Ralstonia solanacearum (Smith) Yabuuchi et al.] is one of the threatening potato diseases. To study the effect of some disease management practices in potato, an investigation was conducted in slightly acidic (pH 5.62) loamy sand soil with medium fertility status in a Randomised Block Design with three replicates and seven treatment modules, as described in Materials & Methods. Investigation revealed that T1 (TPS whole tuber planting) and T4 (supervised management - cowdung
Keywords: Disease Intensity; protective banding; Ralstonia solanacearum; yield loss; potato